Evaluation of equivalent reactions in women after mastectomy using biodex balance system - Kabała, Magdalena; Wilczyński, Jacek (Journal of Education, Health and Sport, 2017)
Abstract Introduction: Breast cancer is the most commonly diagnosed malignant tumour in women in Poland, as well as in developed countries of the world. The unilateral radical mastectomy may result in disturbance of statics and body balance. Disturbances in body coordination may be associated with unevenly distributed tension of postural muscles between left and right side. Aim of the research: Evaluation of equivalent reactions in women after mastectomy on the basis of posturographic examination. Material and methods: 40 women were provided with the study, including 16 female patients (40%) after right-sided mastectomy and 24 female patients (60%) after left-sided treatment. The average age of respondents was 68.5 years. The Postural Stability Test, as well as Sensor Integration and Balance Test on the Biodex Balance System platform were used to evaluate the equivalent reactions. Research was carried out at the Posturology Laboratory of Physiotherapy Institute of the Jan Kochanowski University in Kielce. Results and conclusions: Mann-Whitney U-test showed a statistically significant relation in the Postural Stability Test in dynamic mode between M/L stability index and the side of carried out mastectomy (p=0.027). Women after right-sided mastectomy mostly had lower parameters in dynamic posture, especially in the frontal plane (M/L). Pearson’s correlation coefficient showed a significant relation between the Postural Stability Test in dynamic mode and the Sensor Integration and Balance Test on a soft open-eye surface (p=0.001). The standing position of examined was characterized by higher leavings in the sagittal plane than in the frontal plane (A/P>M//L).